ANALISIS KOMPARASI PROMOSI ONLINE DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN: (Studi Kasus Aplikasi Belanja Online Shopee Dan Lazada Di Surabaya) - Amelia Zulita Purnama Sari (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2022)
In this era, there are many online shopping applications that can make it easier to shop for various products. Especially with the condition of the Covid-19 pandemic where we seem to be faced with a situation where there is no other choice for us (the public) to choose online shopping instead of coming directly to markets or shops that have a greater risk of being exposed to Covid-19. This study aims to determine the difference between Online Promotion and Service Quality on Purchase Decisions on Shopee and Lazada online shopping applications. This study uses quantitative methods with survey research using questionnaires with a sample of 100 respondents who have shopped at Shopee and Lazada at least 2 times in the Suarabaya area which is distributed through the Whatsapp application with the help of friends and relatives who are in Surabaya. The sampling method used in this research is purposive sampling using non-random sampling technique. For processing the questionnaire data that has been distributed using the SPSS 24 application. The results of this study indicate that there is a difference between Online Promotion and Service Quality on Purchase Decisions for Shopee and Lazada online shopping applications in Surabaya. And both of these variables have an effect on the Purchase Decision of Shopee and Lazada. Therefore, it is hoped that in the future, online promotions will be further improved in the form of cashback and free shipping and service quality in the form of providing real pict photos.